Masdevallia sotoana (Orchidaceae: Pleurothallidinae), a new species from Ecuador - Medina, Hugo; Pupulin, Franco (Lankesteriana: International Journal on Orchidology, 2010)
A new species of Masdevallia, M. sotoana, is described and illustrated from Ecuador. The new species is similar to M. strobelii, from which is mainly distinguished by the smaller size of the plant and flowers, the petals provided with a small basal teeth, the narrowly lanceolate lip abruptly reflexed at apex and the much shorter column foot.